Psychological Predictors of Acute Postoperative Pain After Hysterectomy for Benign Causes. Issue 7 (July 2017) - Scheel, Jennifer; Sittl, Reinhard; Griessinger, Norbert; Strupf, Marion; Parthum, Andreas; Dimova, Violeta; Horn-Hofmann, Claudia; Thiel, Falk; Beckmann, Matthias W.; Lautenbacher, Stefan
Abstract : Objectives: Psychological parameters have been shown to contribute significantly to the development of acute postoperative pain (APOP). For the prediction of APOP in chest malformation patients and cancer patients, we found pain-specific psychological predictors to be of higher relevance than general psychological predictors. The current study aims to further substantiate these findings. Materials and Methods: In a sample of 73 middle-aged hysterectomy patients, 3 predictor sets were assessed 1 day before surgery: attentional biases (toward pain-related, social threat, and positive words in a dot-probe task), pain-related emotions and cognitions (pain anxiety, pain catastrophizing, and pain hypervigilance), and affective state variables (depression and somatization). APOP intensity rated 2 to 3 days after surgery and analgesic consumption during the first 48 postoperative hours were used as outcome measures. Results: APOP intensity ratings were significantly explained by their best single predictors in a multiple regression analysis: social threat words of the dot-probe task, pain anxiety, and somatization (14.7% of explained variance). When comparing standardized β coefficients, pain-specific psychological predictors appeared to be of higher explanatory relevance than general psychological predictors. In contrast, analgesic consumption could not be significantly predicted by the psychological variables. Discussion: Hysterectomy patients at risk for high APOP intensity could be characterized by the psychological variables used, whereas their predictive value for analgesic consumption was limited. The high predictive potency of pain-specific psychological variables should be considered for further improvement of pain management and prevention, because pain-specific variables such as pain anxiety can be the target of focal psychological interventions when preparing for surgery.